Prospects for regulatory convergence under TTIP - Suparna Karmakar (Bruegel, 2013)
An ambitious, comprehensive and high-standard trade and investment agreement between the European Union and the United States is feasible, but a key concern is whether the transatlantic trade partners will succeed in creating a meaningful agreement within the tight timeline of the Transatlantic Trade and Investment Partnership (TTIP) negotiations. The target of a ratified pact before a new European Commission takes office in November 2014 is an objective that is likely to conflict with the level of ambition on the substance. Regulatory congruence would require the unilateral and unconditional recognition by the TTIP partners of each other's standards, procedures and conformity assessment tests. The way forward is to create a 'living' (or progressive commitment) agreement on regulatory cooperation with a horizontal template for coherence and conformity assessment and a detailed monitoring mechanism, with implementation starting immediately for a few selected sectors. Regulatory harmonisation under TTIP may not lead to emerging markets automatically upgrading to the higher TTIP standards. Domestic priorities and the high demand from a rising price-sensitive group of consumers will likely result in a dual regulatory regime in emerging markets in the medium-term.
Keywords: 330; Handelsabkommen; Handelsliberalisierung; EU-Staaten; USA